Fabrication of Mesoporous Cu Films on Cu Foils and Their Applications to Dopamine Sensing. Issue 18 (21st August 2017) - Baba, Daisuke; Li, Cuiling; Malgras, Victor; Jiang, Bo; Alamri, Hatem R.; Alothman, Zeid A.; Hossain, Md. Shahriar A.; Yamauchi, Yusuke; Asahi, Toru
Abstract: We previously succeeded to prepare stable mesoporous Cu films on Au‐coated conductive working electrodes by using polystyrene‐ b ‐poly(oxyethylene) (PS63 000 ‐ b ‐PEO26 000 ) micelles as template and sulfuric acid to increase ionic conductivity. In the present study, we report the preparation of mesoporous Cu films on Cu foil. By changing the Cu salts and electrodeposition potentials, we discuss how these parameters influence the final product. Without having to filtrate interefering species, such as uric acid, ascorbic acid and glucose, the dopamine concentration can be precisely determined by applying a suitable potential. Therefore, non‐invasive electrochemical sensing based on mesoporous films will be useful for daily diagnosis of mental disorder. Abstract : Dopamine sensing : The preparation of mesoporous Cu films on Cu foil is reported. By changing the Cu salts and electrodeposition potentials, we discuss how these parameters influence the final product. Without having to filtrate interfering species, such as uric acid and ascorbic acid, the dopamine concentration can be precisely determined by applying a suitable potential.